Development of an augmented reality food application for hawker centres - Tiang, Kristi Jia Wei (Nanyang Technological University, 2024)
AR advertising has been a rising trend in promoting one’s business. It is a fast-growing global market, expected to be valued at USD 597 billion by 2030. Many businesses in the food industry have since tapped into AR technology to enhance consumer experience.